2004
DOI: 10.1021/nl048738s
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Composition of Cu-Doped CdSe Nanocrystals Using Soft X-ray Absorption Spectroscopy

Abstract: The local structure and composition of Cu ions dispersed in CdSe nanocrystals is examined using soft x-ray absorption near edge spectroscopy (XANES). Using Cu L-edge XANES and X-ray photoelectron measurements (XPS), we find that the Cu ions exist in the Cu(I) oxidation state. We also find that the observed Cu L-edge XANES signal is directly proportional to the molar percent of Cu present in our final material. Se L-edge XANES indicates changes in the Se density of states with Cu doping, due to a chemical bondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(178 citation statements)
references
References 32 publications
(61 reference statements)
14
162
1
1
Order By: Relevance
“…Both we 15 and others 19 have argued for Cu(I) doping, leading to a d 10 dopant that is magnetically silent while other groups have found evidence for Cu(II) doping 17,18,21 . As Cu(II) is d 9 , we expect this paramagnetic (s = 1 2 ) center to be magnetically active, and therefore either electron spin resonance or magnetometry should be employed to confirm this oxidation state 18 .…”
Section: B Oxidation State Of Copper Dopantsmentioning
confidence: 53%
See 3 more Smart Citations
“…Both we 15 and others 19 have argued for Cu(I) doping, leading to a d 10 dopant that is magnetically silent while other groups have found evidence for Cu(II) doping 17,18,21 . As Cu(II) is d 9 , we expect this paramagnetic (s = 1 2 ) center to be magnetically active, and therefore either electron spin resonance or magnetometry should be employed to confirm this oxidation state 18 .…”
Section: B Oxidation State Of Copper Dopantsmentioning
confidence: 53%
“…The zinc blende (ZB) structure limits the equation to 4 nearest neighbors and 12 next nearest neighbors. Dopants shall be considered as the reference atom as reports 15 indicate that a dopant substitutionally replaces Cd atoms in the lattice, thus resulting in the maintaining the original geometry. Cations and anions are topologically identical in the ZB system allowing for simplification via symmetry.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Hence, CdSe represents an archetypal system for numerous QD applications (including uses in biomedical imaging and laser diodes) and an ideal model for the study of quantum confinement effects. Although extensive research has been devoted to characterization of the electronic structure in CdSe QDs, [4][5][6][7][8][9] the sizedependent evolution of the valence band (VB) and CB-DOS remain unresolved from one another via experimental study. It has been demonstrated that theoretical calculations provide a means for the deconvolution and isolated study of the VB and CB.…”
Section: Pacs Numbersmentioning
confidence: 99%